How are small businesses adapting to the new normal? Examining tourism development amid COVID-19 in Phuket. Issue 24 (17th December 2021) - Fuchs, Kevin
ABSTRACT: It is reasonable to state that Thailand's economic impact had been severe due to the lack of international tourists. In particular, the mass-tourist destination Phuket has suffered economic consequences as the result of plunged international passenger arrivals, and inadequate domestic tourists to fill their place. The objective of the paper is to identify inadequacies that help stakeholders to manage tourism development amid COVID-19 more effectively. The empirical data for this study was collected through a series of semi-structured interviews (n = 21) with local small business owners. The study offers insights into the recent tourism development during the COVID-19 global pandemic and discloses a high level of resilience amongst the small local business owner community. The majority of small business owners were able to seize opportunities through the adaptation of their business models that have the potential for long-term success.